Clinico-epidemiological profile of dermatology patients: a one-year study at a newly established tertiary care centre in India - Singh, Shradha; Geetha, K.; Upadhyaya, Amrita; Gusain, Teesta (International Journal of Research in Dermatology, 2024)
Background: Dermatology is predominantly an outpatient specialty focused on the diagnosis and treatment of dermatoses affecting the skin. We conducted a study on the demographic and clinical characteristics of patients attending the outpatient clinic to better understand the clinico-epidemiological profile and to predict morbidity patterns within the specific geographical region. Methods: A retrospective study was conducted over the past year, encompassing all patients who visited the outpatient dermatology clinic at AIIMS, Raebareli. The study systematically documented a range of dermatoses, including disorders affecting the skin, hair, and nails. Results: A total of 4,188 patients were included in the study, comprising 2,681 (64%) adults, 978 (23.4%) geriatric patients, and 529 (12.6%) pediatric patients. Among these, 1,311 patients primarily suffered from infections, followed by 752 patients with dermatitis. Of those with infections, 1,024 (78%) were diagnosed with fungal infections, while scabies was observed in 126 patients (9.6%). In the adult group, 756 (28.2%) patients had infections, while 429 (16%) patients were affected by dermatitis. Similar patterns were observed in both the geriatric and pediatric groups, with infections being the most prevalent, affecting 214 and 341 patients, respectively. Conclusions: Based on the findings of this study, it can be concluded that infections, particularly fungal infections, are the most prevalent dermatological conditions across all age groups in the population studied. Dermatitis also emerged as a significant concern, particularly among adult patients. The high prevalence of infectious dermatoses, especially in geriatric and pediatric patients, highlights the need for targeted public health interventions and preventive measures.